On the Relative Catch Efficiency of Different Shaped Otter Boards in Bottom Trawling - NARAYANAPPA, G. (Fishery Technology, 1968)
Three different types of otter boards varying in shape were tried to find out their relative catch efficiency. They were operated with two types of nets. The results indicated that the curved otter boards gave more catch per unit effort with all the combinations of nets and riggings tried.